Kajian Transformatif Trias Politika dalam Demokrasi Kemahasiswaan Perguruan Tinggi Swasta di Malang. - Lidia Nora Putarata; Engelbertus Kukuh Widijatmko; Andri Fransiskus Gultom (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Indonesia is a legal state that operates a democratic system and makes the people the highest authority. Democracy implemented in Indonesia uses the political triad concept, namely the division of power into three axes. However, the people as the holders of the highest power are now starting to have little awareness of participating in democracy. This of course has a negative impact on the life of democracy in Indonesia. So it is important to have outreach that discusses the role of the people in democracy. Socialization can be done in various ways and in any place, including educational places. In education, socialization can be carried out by implementing the same democratic system as Indonesia and making the target of socialization the executor of the course of democracy. However, the most strategic and appropriate level of education to carry it out is at the student level. Students are the most appropriate level because they are the highest level of education and are also the young generation who are ready to be prepared to enter politics. So, researchers conducted research to find out the effect of implementing the trias politica system in a higher education environment on community participation in politics itself. Researchers use qualitative research methods to explain the depth of the problem being studied. Researchers also use a case study approach to obtain and collect data in research, for example finding a system for implementing the trias politica concept in revitalizing democracy among students, especially private university students in the city of Malang.